Development and evaluation of rheological and bioactive properties of rice protein-based gels. (November 2016) - Felix, M.; Romero, A.; Guerrero, A.
Abstract: The rice industry produces a large amount of by-products daily. In fact, it is estimated that approximately 100 million tons of rice residues and by-products are generated each year. However, new protein sources are demanded for human food because of the continuous increase in the global population coupled with the almost total inability to increase global food production. A rice protein concentrate (RPC), which is a by-product of the rice industry, and two different hydrolysates (RPH25 and RPH120 ) obtained from RPC, have been used in order to evaluate the potential of RPC to form a gel-like food product at three different pH values (2.0, 6.5 and 8.0). The gelation process was monitored and subsequently, mechanical spectra were obtained. In addition, protein interactions (ionic interactions, hydrophobic interactions, hydrogen bonds and disulphide bonds) were also determined in order to understand the gel structure. Finally, an antioxidant characterisation was carried out using three different reagents: DDPH, ABTS and Folin-Ciocalteu. A proper degree of hydrolysis and an optimal pH value seem to be key factors in the manufacturing of gels, showing a remarkable influence on both rheological properties and antioxidant activities. Highlights: A suitable degree of hydrolysis is desirable for the formation of a proper gel-network. The pH value has a high influence on the gel properties. The hydrolysis plays a fundamental role in the antioxidant response. The antioxidant activity also is highly pH-dependent.